Effects of Touching Sculptures on the Artistic Appreciation of Collative Emotional/Perceptual Properties - Bueno, José Lino de Oliveira; Motta, Márcia Regina; Tumas, Vitor (Paidéia (Ribeirão Preto), 2020)
The relationship between physical stimulus and perception is fundamental to understand aesthetic appreciation. This study aimed to examine how the properties of sculptures influence their artistic appreciation. Thirteen participants touched altered sculptures from the series Bichos de Lygia Clark. Participants indicated their perceptions for each stimulus using Semantic Differential Scales (7-point Likert scale): Complexity, Irregularity, Amount of pieces, Interest and Pleasingness. The duration of manipulation was recorded. The results showed that sculptures perceived as having more pieces were the ones judged to have a high level of Complexity and Irregularity. Sculptures evaluated as demonstrating a high level of Complexity and Irregularity were considered more interesting, although less pleasant. Participants tended to spend more time exploring the more complex sculptures. The results indicate that the amount of informational content, represented by the amount of pieces present in the sculpture, can influence the way it is perceived and affect its hedonic value.